Teacher Activities and Adolescent Students' Participation in a Colombian EFL Classroom - Jefferson Caicedo (Universidad Nacional de Colombia, 2015)
The present study concerns the activities teachers develop and ninth-graders' participation in responses to those activities. The objectives of this study were to identify and describe the types of teaching activities developed and how students respond to them and to show how the target language is used in the classroom. The data collection was conducted through daily field notes and a diary. The findings show that in the classroom, the teacher develops twelve types of activities, and the percentage of use of the target language is low.